Position-related differences in selected morphological body characteristics of top-level female handball players - Bon, M.; Pori, P.; Sibila, M. (Collegium Antropologicum, 2015)
The study aimed to establish the main morphological characteristics of Slovenian junior and senior female national handball team players. Morphological characteristics of various player subgroups (goalkeepers, wings, back players and pivots) were also determined so as to establish whether they had distinct profiles. The subjects were 87 handball players who were members of the Slovenian junior and senior female national teams in the period from 2003 to 2009. A standardised anthropometric protocol was used to assess the subjects` morphological characteristics. The measurements included 23 different anthropometric measures. First, basic statistical characteristics of anthropometric measures were obtained for all subjects together and then for each group separately. Somatotypes were determined using Heath-Carter`s method. Endomorphic, mesomorphic and ectomorphic components were calculated by computer on the basis of formulas. In order to determine differences in the body composition and anthropometric data of the subjects playing in different positions, a one-way analysis of variance was employed. The results show that, on average, the wings differed the most from the other player groups in terms of their morphological body characteristics. The wings differed most prominently from the other player groups in terms of their morphological body parameters as they were significantly smaller and had a statistically significantly lower body mass than the other groups. In terms of transversal measures of the skeleton and the circumferences, the wings significantly differed mainly from the pivots and goalkeepers and less from the backs. The goalkeepers were the tallest, with high values of body mass and low values of transversal measures compared to P. Their skin folds were the most pronounced among all the groups on average and their share of subcutaneous fat in total body mass was the highest. Consequently, their endomorphic component of the somatotype was pronounced. Players in the Pivot position were significantly taller than the W players but were not significantly different from G and B. They had high values of body mass which were significantly higher than that of W but did not differ significantly from the body mass values of B and G. The average values of their circumferences were the highest among all the player groups and the same is true for transversal measures of the skeleton. It is very interesting that, compared to the players in other playing positions, they achieved low values of subcutaneous fat. Their values of the somatotype revealed an endo-mesomorphic somatotype, with a pronounced mesomorphic component. Back players were tall and had the lowest share of subcutaneous fat of all the player groups. Significant differences were established mainly in terms of the structure of the lower extremities. The values of the somatotype characteristics were very balanced between all three components. The results of our study confirm that groups of handball players occupying different positions differed amongst themselves in terms of many measurements. This is a result of the specific requirements of handball play which are to be met by particular players. The tallest players should thus be oriented to back player positions. As regards pivots, the coaches must, besides body height, consider robustness. For goalkeepers, body height is very important; however, the robustness criteria are slightly lower. For wings, body height is not a decisive factor and smaller players can also occupy this position. Both of the above (also taking other criteria into account) facilitate coaches` decisions when orienting players into their playing positions.